The Influence of Electronic Word of Mouth on Instagram Towards Visiting Interest to Heha Ocean View - Chandra Dewa Kurniawan; Amali, Muhammad Thoyib (Jogjakarta Communication Conference (JCC), 2024)
Heha Ocean View is a tourist attraction in Gunungkidul, Special Region of Yogyakarta. Many visitors are willing to come for tours even though it is far from the city center. It provides various interesting photo spots with a sea background that can be called Instagramable. Therefore, Heha Ocean View has become a topic of conversation on various digital platforms. Especially on Instagram, resulting in community engagement in the form of electronic word of mouth which spreads this tourist attraction. This study aims to analyze the influence of electronic word of mouth on Instagram towards visiting interest to heha ocean view. This research uses explanatory quantitative research methods with data obtained from questionnaires distributed to 100 followers of the @HehaOceanView Instagram account, which is then analyzed using simple linear regression. The results of this study show the influence of electronic word of mouth on Instagram towards visiting interest to Heha Ocean View with an influence size of 53%. Based on the results of the analysis, it can be concluded that in this digital era, there are many ways to achieve community engagement, one of which is through electronic word of mouth through digital platforms such as Instagram. Like how electronic word of mouth can make tourists interested in visiting Heha Ocean View. However, as active users of social media, we must always be critical of the information we obtain, especially if we look at how electronic word of mouth shapes individual attitudes and behavior.